Degradation kinetics of pelargonidin-3-(p-coumaroyl)diglucoside-5-(malonyl)glucoside and pelargonidin-3-(feruloyl)diglucoside-5-(malonyl)glucoside in red radish during air-impingement jet drying. (June 2020) - Li, Wenfeng; Pang, Xinxin; Xiao, Jinfeng; Wang, Xinyu; He, Ruiyan; Zhao, Xin
Abstract: Red radishes were dried using air-impingement jet drying (AIJD) at different temperatures of 50 °C, 60 °C, and 70 °C. The color displayed a significant change, while the total anthocyanin content (TAC), and DPPH· and ABTS ·+ scavenging activities were dramatically decreased in AIJD-dried red radishes compared to fresh red radishes. Using UHPLC-QqQ-MS/MS analysis, eight pelargonidin glucosides and two cyanidin glucosides were identified in red radishes. The pelargonidin-3-( p -coumaroyl)diglucoside-5-(malonyl)glucoside (P3PD) and pelargonidin-3-(feruloyl)diglucoside-5-(malonyl)glucoside (P3FD) signified the two primary anthocyanins in red radishes. AIJD caused the degradation of P3PD and P3FD while following the second-order kinetic equation. The degradation rate and half-life (t1/2 ) of the P3PD degradation increased with the elevation of the AIJD temperature, while that of P3FD decreased. The enthalpy of activation presented values between 2.87 kJ/mol and 3.04 kJ/mol for P3FD, and between 37.07 kJ/mol and 37.23 kJ/mol for P3PD. The positive ΔG suggested that the degradation of P3PD and P3FD was a non-spontaneous reaction. The transition state displayed lower structural freedom than the P3PD and P3FD, as evidenced by the negative ΔS. These results could contribute to inhibiting the degradation of anthocyanins in red radishes during processing. Graphical abstract: Image 1 Highlights: Air-impingement jet drying changed the anthocyanin content of red radish. There are eight pelargonidin glucosides and two cyanidin glucosides in red radish. As one of the main anthocyanins, P3FD displays the highest levels. The degradation of P3PD and P3FD were non-spontaneous, endothermic reactions.